Manajemen Sarana dan Prasarana di SD Karakter Anna Cendekia Insani Bangkalan - Putri Masita, Farah; Muharromah Pratiwi Putri, Estin; Betananda Rustiawan, Salsabilla (JOURNAL OF EDUCATION FOR ALL, 2023)
This study aims to determine the management of facilities and infrastructure at Anna Cendekia Insani Character Elementary School. The research design used in this research is qualitative research. The data collection technique in this study, namely through observation of the facilities and infrastructure in schools and interviews with one of the teachers. The research instruments used in the research were observation sheets and interviews. This research was conducted at Anna Cendekia Insani Character Elementary School. The results of the study show that in the planning management of Anna Cendekia Insani Character Elementary School, which initially only had grade 1 students, it planned to add more classes in the following school year. Apart from that, in procuring facilities and infrastructure at SD Character Anna Cendekia Insani, namely by collecting data. In the management of facilities and infrastructure, inventory or checking is also carried out within one week. In maintaining the facilities and infrastructure is also carried out every three months. The deletion of school facilities and infrastructure has never been done.